1990
DOI: 10.3354/meps066225
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle and distribution of Calanus finmarchicus in deep basins on the Nova Scotia shelf and seasonal changes in Calanus spp.

Abstract: The deep basins on the Nova Scotia shelf contain high concentrations of Calanus finmarchicus, C. glacialis, and C. hyperboreus at depths below 200 m. From May to late fall these were as high as 20 000 m-3. The dominant specles by numbers was C. finmarchicus; however, its biomass was equalled or exceeded by C. hyperboreus. The life cycle of C. finmarchicus in the region of 2 of the largest basins showed that breeding started late in winter with a peak in April. High concentrations of Calanus suggested that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 10 publications
3
37
1
Order By: Relevance
“…A similar pattern was found for C. paci$cus in Dabob Bay, a fjord in Washington (Osgood and Frost 1996). In addition, the deep Scotian Shelf basins accumulate high concentrations of latestage copepodids of C. jinmarchicus, Calanus hyperboreus, and Calanus glacialis (Sameoto and Herman 1990;Herman et al 1991).…”
supporting
confidence: 67%
“…A similar pattern was found for C. paci$cus in Dabob Bay, a fjord in Washington (Osgood and Frost 1996). In addition, the deep Scotian Shelf basins accumulate high concentrations of latestage copepodids of C. jinmarchicus, Calanus hyperboreus, and Calanus glacialis (Sameoto and Herman 1990;Herman et al 1991).…”
supporting
confidence: 67%
“…Since the data already indicate population centers over the basins, these are potentially very important. Sameoto & Herman (1990) and Herman et al (1991) found this to be the case in the deep basins on the Scotian Shelf; it is reasonable to anticipate the same in the Gulf of Maine. We imagine, therefore, deep unexplored reservoirs of diapausing copepodites within the 200 m isobaths.…”
Section: Mmentioning
confidence: 71%
“…This is the same mechanism proposed for the high concentrations of deep-dwelling stages of Calanus spp. in basins on the Nova Scotia shelf (Sameoto & Herman 1990). Advection of organisms to a n area combined with a concentrating mechanism is also the explanation Wishner et What happens to the deep aggregation?…”
Section: How Does the Deep Aggregation Build Up?mentioning
confidence: 99%